2018
DOI: 10.3892/or.2018.6308
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of aquaporin 3 in prostate cancer is regulated by RalA

Abstract: We previously found that in normal epithelia of the prostate, localization of AQP3 is limited to the cell membranes; however, the expression of AQP3 protein in cancer epithelia is distributed to the plasma. Yet, the detailed mechanism remains unclear. In the present study, PC‑3 cell derivatives with stable knockdown of RAS like proto‑oncogene A (RalA) and overexpression of E‑cadherin were established. We found that overexpression of E‑cadherin and knockdown of RaLA resulted in an increase in AQP3 in prostate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Trafficking may depend on the phosphorylation of monomers, AQP2 needs phosphorylation of at least three monomers to determine its position in the plasma membrane [ 33 ]. In prostate cancer cells, PC-3, AQP3 is translocated from the cytoplasm to the cell membrane after silencing of RAS like proto-oncogene A (RalA) [ 34 ]. Regulation of the flux through the channel is referred to as gating and is regulated by pH, phosphorylation, temperature, membrane tension, solvent gradient, and pressure [ 24 , 35 , 36 ].…”
Section: Aquaporinsmentioning
confidence: 99%
“…Trafficking may depend on the phosphorylation of monomers, AQP2 needs phosphorylation of at least three monomers to determine its position in the plasma membrane [ 33 ]. In prostate cancer cells, PC-3, AQP3 is translocated from the cytoplasm to the cell membrane after silencing of RAS like proto-oncogene A (RalA) [ 34 ]. Regulation of the flux through the channel is referred to as gating and is regulated by pH, phosphorylation, temperature, membrane tension, solvent gradient, and pressure [ 24 , 35 , 36 ].…”
Section: Aquaporinsmentioning
confidence: 99%
“…Nejsum and Nelson, (2007) confirmed that AQP3 co-localizes with E-cadherin during the early stages of cell-cell contact formation [82]. AQP3-E-cadherin co-localization depends upon the level of E-cadherin and increased E-cadherin levels simultaneously increase AQP3 expression in the plasma membranes of prostate epithelial cells [83]. Another study reported that the knockdown of RAS such as proto-oncogene A (RalA) facilitates increased AQP3 expression onto the plasma membrane [83].…”
Section: Aquaporin Expression In Prostate Cancermentioning
confidence: 89%
“…Genetic knockdown of AQP1 in rat granulosa and Chinese hamster ovary cells was associated with protection from cell shrinkage and apoptosis [86]. AQP3, located in plasma membranes of human prostate tissue and benign tumors, was found to be internalized in prostate cancer cells, again consistent with a reduction in AQP functionality promoting resistance to apoptosis [87]. In contrast, other cases involving AQP1 and AQP5 have yielded opposite outcomes, in that the presence of the functional channel was protective, and loss of function promoted cell death.…”
Section: Aqps In Apoptosismentioning
confidence: 89%